PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA KELAS VIII SMP BERBASIS KONSTRUKTIVISME - Nilam Purnama Sari (Jurnal Edukasi dan Penelitian Matematika, 2018)
The aim of this research was to design teaching matherial of Mathematics based on constructivism that valid, practical, and effective for 8th grade students. Plomp’s development procedure was applied to conduct the study, which covers three stages: Preliminary, Prototyping, Assesment. This research was conducted at SMP NEGERI 1 Padang. The subject was 32 students of class VIIID and the object was teaching matherial of Mathematic. Kind of the data took directly of questionnaire and test. Instrument of collecting data was questionnaire of validity and practicality. The data taken then analyzed by descriptive analysis technique. The teaching matherial of development result have been validated with validation result of RPP was 87,85% (valid) and LKPD was 91,78% (very valid) then practicality result of RPP was 81,33% (practical) and LKPD was 73,33% (practical).Teaching matherial of Mathematic based on constructivism have been successed for facilitate student’s concept constructing proved by 26/32 (81,25%) students passed the final test.Keywords—learning matherial, constructivism, validity, practicallity, affectivism.